2000
DOI: 10.1016/s0014-5793(00)02249-3
|View full text |Cite
|
Sign up to set email alerts
|

Generation and degradation of human endostatin proteins by various proteinases

Abstract: The angiogenesis inhibitor endostatin is a fragment of the NC1 domain of collagen XVIII. The generation of endostatin has been investigated only in murine hemangioendothelioma cell cultures and was ascribed to cathepsin L. Distinct endostatin-like fragments were detected in human tissues and serum. To identify proteinases able to generate such fragments, we incubated human NC1 with proteinases of all classes, including cathepsin L. Eleven out of 12 generate fragments with an N-terminus within the same 15 resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
261
2
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(274 citation statements)
references
References 28 publications
4
261
2
7
Order By: Relevance
“…However, the pro-angiogenic role of MMPs has been challenged by the recent findings that some MMPs (MMP2/3/7/9/12/13/14/20) can process and generate angiogenesis inhibitors like angiostatin or endostatin to inhibit endothelial cell proliferation, migration, and angiogenesis. [38][39][40][41][42] The role of MMP19 in cancer is as controversial as for all other MMPs. MMP19 is up-regulated in astroglial tumor and melanoma 43,44 and reported to increase human keratinocyte cell proliferation, migration, and adhesion on type I collagen through the IGF-signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pro-angiogenic role of MMPs has been challenged by the recent findings that some MMPs (MMP2/3/7/9/12/13/14/20) can process and generate angiogenesis inhibitors like angiostatin or endostatin to inhibit endothelial cell proliferation, migration, and angiogenesis. [38][39][40][41][42] The role of MMP19 in cancer is as controversial as for all other MMPs. MMP19 is up-regulated in astroglial tumor and melanoma 43,44 and reported to increase human keratinocyte cell proliferation, migration, and adhesion on type I collagen through the IGF-signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…37 On the other hand, recent reports have demonstrated that the generation of endostatin, an inhibitor of angiogenesis and tumor growth, is catalyzed by proteolytic enzymes, including cathepsin L and matrix metalloproteases. 38,39 However, cathepsin L as well as cathepsin B has been implicated in malignant transformation, 40,41 metastatic tumor growth and poor prognosis. [42][43][44] In particular, secreted and membrane-associated cathepsins appear to play an important role in metastasis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Endostatin, a 22-kDa fragment of collagen XVIII, is a member of a group of endogenous antiangiogenic proteins (O'Reilly et al, 1997) that are activated by proteolytic processing (Ferreras et al, 2000). In fact, the antiangiogenic activity of endostatin is speculated to be specifically mediated by the inhibition of endothelial cell adhesion, migration and proliferation, and induction of apoptosis (Dhanabal et al, 1999).…”
mentioning
confidence: 99%